2019
DOI: 10.15832/ankutbd.440179
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Tolerance of Commercial Onion Cultivars to Stem and Bulb Nematode Ditylenchus dipsaci

Abstract: Nematode resistance and tolerance reactions of 28 onion cultivars grown commercially in Turkey to stem and bulb nematode were studied at 20 °C, 70% RH and 16:8 h L:D photoperiod in growth chamber with 10 replications and at 27±4 °C and 16:8 h L:D photoperiod in greenhouse with 3 replications, respectively. Ditylenchus dipsaci multiplied in all cultivars tested. The lowest multiplication was determined in cv. Valenciana from Atatürk Horticultural Central Research Institute with 91 nematodes/pot and a multiplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…However, there are few studies focused on resistance of the onion to D. dipsaci. Yavuzaslanoglu et al (2015Yavuzaslanoglu et al ( , 2019 reported some commercial cultivars providing lower nematode multiplication and tolerance to D. dipsaci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few studies focused on resistance of the onion to D. dipsaci. Yavuzaslanoglu et al (2015Yavuzaslanoglu et al ( , 2019 reported some commercial cultivars providing lower nematode multiplication and tolerance to D. dipsaci.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports on resistant and tolerant oat, rye, beans, potato and clover cultivars which are host of D. dipsaci (Plowright et al 2002;Mwaura et al 2015). Previous studies reported commercial onion cultivars that provided low nematode reproduction and tolerance to D. dipsaci, under controlled and field conditions (Yavuzaslanoglu et al 2015;Yavuzaslanoglu 2019).…”
Section: Research Article/araştırma Makalesi 196mentioning
confidence: 99%
“…Plowright et al (2002) reported high resistance against D. dipsaci in a faba bean line, which has been used to develop resistant cultivars for North Africa. Despite variations in the nematode reproduction rate among onion (Allium cepa L.) cultivars, Yavuzaslanoglu (2019) found no resistance towards D. dipsaci. Caubel et al (1994) demonstrated a positive relationship between symptom expression at 3 weeks postinoculation and D. dipsaci reproduction at 10 weeks postinoculation on red clover.…”
Section: Introductionmentioning
confidence: 87%
“…Onion plants of the variety Betapanko (Beta Seeds, Konya, Turkey), which is susceptible to the stem and bulb nematode (Yavuzaslanoglu 2019), were grown from seed sown in two plastic pots (17x15x15 cm) containing 6 L of field soil autoclave-sterilised at 121 ℃ for 120 minutes, then treated or untreated with mycorrhizae, at 20 ℃, 70% humidity and 16: 8 hours day: night period, in a growth chamber.…”
Section: Growing Onion Plants For the Experimentsmentioning
confidence: 99%
“…The stem and bulb nematode develops in the intercellular spaces in the aboveground parts of the onion plant, causing the disintegration of the tissues and changes in the plant's physiology. It decreases market value by causing rotting of onion tubers (Yavuzaslanoglu 2019).…”
Section: Introductionmentioning
confidence: 99%